Understanding the colloidal behaviour or 45S5 bioactive glass particles to obtain bioactive-glass based composite coatings by EPD - Cabanas Polo, Sandra; Boccaccini, Aldo R. (Key Engineering Materials, 2015)
The interaction between bioactive glass particles and polymers with different functional groups has been established in this work to better understand and control the colloidal processing of the bioactive glass phase. Cationic polyvinylpyrrolidone (PVP), anionic polyacrylic acid (PAA) and neutral polyvinyl alcohol (PVA) were selected and the surface reactions in alcoholic media and between bioactive glass particles and polymers were considered. All three polymers were successfully employed to obtain soft composite coatings incorporating bioactive glass particles.
Keywords: Bioactive glass; Colloidal stability; EPD; Synthetic polymer